2016
DOI: 10.1111/1467-923x.12226
|View full text |Cite
|
Sign up to set email alerts
|

The Curious Incident of Mr Cameron and the United Kingdom Defence Budget: A New Legacy?

Abstract: During 2015 Prime Minister Cameron found himself under intense domestic and international pressure over his apparent reluctance to maintain United Kingdom defence spending at the NATO target level of 2 per cent of GDP. Most commentators attributed this reluctance to the inevitability of defence cuts if the government wished to meet its deficit reduction targets. However, the aftermath of the general election saw a sudden decision to maintain UK defence spending at the NATO target level. This u-turn is one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The UK's most recent five-yearly SDSR made no reference to the CSDP as a component of the UK's approach to providing for its national security and defence (but does stress bilateral defence and security relationships with France, Germany and Poland). 58 On the operational aspects of the CSDP, the UK has not been willing to engage at a level of significant scale and scope with CSDP military operations, and generally sees itself as having a preference for NATO-focused commitments. Consequently, London has been a modest contributor to the EU's military operations, although it has committed personnel to the majority of the EU's 'civilian' missions deployed for roles such as border observation and capacity-building for third countries.…”
Section: The Potential Costs To the Eu Of Brexitmentioning
confidence: 99%
“…The UK's most recent five-yearly SDSR made no reference to the CSDP as a component of the UK's approach to providing for its national security and defence (but does stress bilateral defence and security relationships with France, Germany and Poland). 58 On the operational aspects of the CSDP, the UK has not been willing to engage at a level of significant scale and scope with CSDP military operations, and generally sees itself as having a preference for NATO-focused commitments. Consequently, London has been a modest contributor to the EU's military operations, although it has committed personnel to the majority of the EU's 'civilian' missions deployed for roles such as border observation and capacity-building for third countries.…”
Section: The Potential Costs To the Eu Of Brexitmentioning
confidence: 99%
“…An early 2016 scholarly assessment of the 2015 SDSR observed that the December 2015 parliamentary vote authorizing air strikes in Syria was a sign that the UK was moving from strategic shrinking to greater international engagement while also maintaining it was to early to determine if spending 2% of GDP on defense would be sufficient to meet national security aspirations. 56 Civilian and military British national security policy analysts and policymakers must engage in ongoing reviews and updates of domestic and international economics, public opinion, military capabilities, and strategic trends and developments to determine if the 2015 SDSR satisfactorily addresses Britain's emerging national security requirements.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, what is less clear is that by choosing a planned change strategy, a new equilibrium was found. The 2015 SDSR updated version evidenced a knowable end‐stage; however, to the eyes of many commentators, it only gave continuity to the already established areas of main change: personnel reductions, revamping the MoD, and cost‐cutting waste in the overall defence governance (see Dorman, Uttley, and Wilkinson 2016).…”
Section: Understanding Changementioning
confidence: 99%
“…Governments balancing their budgets in a period of fiscal austerity are faced with the problems of managing delivery demands while trying to cut back the rising burden of expensive public services (Hunt 2011; McTaggart and O'Flynn 2015; Solar and Smith 2020a, 2020b). During the first half of the 2010s, for example, Western industrialized nations sought to scale down the size of defence saving on personnel, civilian workforce, equipment, and capabilities, while proposing new ways of managing the sector during austerity (see Dorman, Uttley, and Wilkinson 2016; The Economist 2017; Taylor 2012). In Australia, the central government launched Project Suakin after years of inertia, to create a more flexible and adaptable defence, seeking “maximum efficiency” in the workforce (Latham and Sawyer 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation